Woodworking for young makers : fun and easy do-it-yourself projects - Blankenship, Loyd; Boyd, Lane (Maker Media, 2017)
Learning to be a maker has never been more fun. Full-color cartoons and drawings lead you through the steps needed for making a wizard wand, a sanding block, a charging station for your phone or tablet, and a sturdy box with a hidden compartment. You'll learn how to choose and use the right tools, measure and cut properly, sand, glue, and finish your woodworking projects to make them look great. This is the perfect guide for young people who want to do woodworking at home, at school, or at a local makerspace. It teaches fundamental skills and unlocks creativity. No prior experience or knowledge of tools is required. Everything you need to know is explained in the text and cartoons. This easy-to-follow guide is suitable for all ages. It features: Lavish cartoons and line artStep-by-step instructions with full-color artProjects that are fun and usefulBasic skills, handy tips, and safety precautions Woodworking is the most universally useful of crafts. In this book, young adults will learn to work successfully with standard hand tools found in any garage or basement workshop and in any school shop class. The skills learned here will unlock a lifetime of useful skills and satisfying accomplishments.